Sustainable Management of the Fisheries Sector in Oman : A Vision for Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2017)
Fishery and aquaculture are among the most ancient and important sectors of Oman economy, with deep cultural and social significance. Before oil was discovered in the 1960s, 80 percent of the population lived from agriculture and fishing. However currently fishing is not economically productive. Many fishers are not involved full time in fishing, and despite significant subsidies, remuneration is often low. There is a need to improve economic management of the fisheries sector and create viable and sustainable employment opportunities. As a starting point, the Sultanate engaged the World Bank to assist in its effort to overhaul the fisheries sector, and help devise a plan for increasing the contribution that fisheries make to Oman's economy. This review offers a summary of the collaborative efforts involving the Ministry of Agriculture and Fisheries Wealth (MAFW), the World Bank (WB), and fishery stakeholders. Collaborative work laid rigorous groundwork for the development and implementation of the Fisheries and Aquaculture Vision 2040: "To create a profitable world-class sector that is ecologically sustainable and a net contributor to Oman’s economy." Vision 2040 and an accompanying Implementation Plan establishes a framework and processes to achieve these goals. The preparatory work has produced the Sultanate of Oman Fisheries and Aquaculture Vision 2040; the Implementation Plan of the Fisheries and Aquaculture Vision; and a proposed investment project document. The next stage includes implementation of the pilot investment project and technical support, as well as stakeholder co-management of four pilot fisheries. This strategy points to a better future in fishing higher-value species. Phase II, the first five years of implementing Vision 2040, will establish the policy and capacity for executing global best practices in the fisheries through organizational development, business development and management training, as well as planning for new institutions built around key players.